Significantly improving enzymatic saccharification of high crystallinity index's corn stover by combining ionic liquid [Bmim]Cl–HCl–water media with dilute NaOH pretreatment. (August 2015) - He, Yu-Cai; Liu, Feng; Gong, Lei; Zhu, Zheng-Zhong; Ding, Yun; Wang, Cheng; Xue, Yu-Feng; Rui, Huan; Tao, Zhi-Cheng; Zhang, Dan-Ping; Ma, Cui-Luan
Graphical abstract: Highlights: Effective combination pretreatment was successfully demonstrated. After the combination pretreatment, high enzymatic saccharification rates were obtained. High crystallinity index (CrI) of corn stover (50 g/L) was effectively saccharified. The recovered hydrolyzates could be fermented into ethanol efficiently. The combination pretreatment shows high potential application in future. Abstract: In this study, a pretreatment by combining acidified aqueous ionic liquid 1-butyl-3-methylimidazolium chloride (IL [Bmim]Cl) solution with dilute NaOH extraction was employed to pretreat high crystallinity index (CrI) of corn stover before its enzymatic saccharification. After NaOH extraction, [Bmim]Cl–HCl–water (78.8:1.2:20, w/w/w) media was used for further pretreatment at 130 °C for 30 min. After being enzymatically hydrolyzed for 48 h, corn stover pretreated could be biotransformed into reducing sugars in the yield of 95.1%. Furthermore, SEM, XRD and FTIR analyses of untreated and pretreated corn stovers were examined. It was found that the intact structure was disrupted by combination pretreatment and resulted in a porous and amorphous regenerated cellulosic material that greatly improved enzymatic hydrolysis. Finally, the recovered hydrolyzates obtained from the enzymatic hydrolysis of pretreated corn stovers could be fermented into ethanol efficiently. In conclusion, the combination pretreatment shows high potential application in future.